Application of interactive teaching methods in the course of teaching the discipline "History of the Ancient Worldʺ - Bakumenko , O.O. (Problems of Engineer-Pedagogical Education, 2023)
The article examines the use of interactive learning methods in the course of teaching one of the normative disciplines for students of the specialty 032, History and Archeology. The course "History of the Ancient World" is one of the most important subjects for future historians in the process of acquiring professional competences. Its study involves the formation of a holistic view of the development of the world historical process from ancient times to the present day. The high saturation of the course with historical facts and events requires both the students and the teacher to put in a lot of effort for the fruitful organization of the educational process in order to obtain relevant program learning outcomes. The modern education system has created training standards that provide for the training of highly qualified specialists who possess the entire set of systematized theoretical knowledge and practical skills, know how to apply modern technologies, etc. A modern specialist must possess such personal qualities as mobility, creativity, critical thinking, communication skills, ability to make non-standard decisions and bear responsibility for them. It is possible to form such qualities only if conditions are created in the learning process that will encourage students to conduct creative search, give them the opportunity to learn the ropes of working in a team, simulate various situations in education and professional activities. It is precisely the solution of such tasks that contribute, first of all, to interactive learning methods, which have been used fruitfully for a long time in the higher education system of Ukraine. In the article, we offer an analysis of the applied use of interactive learning methods within the framework of teaching a specific educational discipline, which is important in the context of the formation of professional competences of a history specialist. The article considers several basic methods of interactive learning, which are most often used by teachers of our department when teaching subjects of the normative cycle. The review of the methods is accompanied by a description of specific educational situations and conclusions about the influence of one or another method on the formation of program learning outcomes. The author concludes that interactive teaching methods, when used intelligently in combination with classical lectures, require all participants in the educational process to develop communication, argumentation and discussion skills, and tolerance for other people's opinions. The effectiveness of using various forms of interaction in education also depends on the extent to which students understand their relationship with their future profession. We note that this factor is definitely very important for the graduates of our vocational education training program, because they must not only learn historical material, but also be able to apply it in local history and tourism activities, be able to convey interesting material to their listeners, orient themselves in any cognitive situation that may arise during their professional activities.